APPLICATION OF SALAM CONTRACT ON DWATCH COMAL WATCH AGENT DROPSHIP SYSTEM - Muhsin Hariyanto; Muhammad Khoirul Anwar (SEAN Institute, 2023)
This research was conducted to examine the application of buying and selling carried out by Dwatch Comal watch dropshippers from the point of view of buying and selling with a salam contract (bai' salam), with this research it is hoped that it can be known how the application of the salam contract buying and selling system in buying and selling, whether it is in accordance with the principles of Islamic shari'a or not. This research uses qualitative research methods and is a field research. The primary data source is Dwatch Company Management and Customers, consisting of Dwatch owners, dropshyper, consumers, and the Shari'ah Supervisory Board. The data validity technique used in this study is the Source Triangulation Technique. The results of his research showed that from the application of buying and selling with the dropship system carried out by agents or dropshippers of Dwatch Comal watches, it was found that if viewed from the point of view of buying and selling using a salam contract (bai' as-salam), the application of dropshipping by Dwatch watch dropshippers was not fully in accordance with buying and selling salam contracts. The discrepancy is in the payment system, sometimes agents or dropshippers allow buyers to make payments at the end or at the time of handover of goods, which in the end if the payment is made at the end, the sale and purchase is not in accordance with the terms of sale and purchase of the salam contract, so that when viewed from the point of view of bai' as-salam, the application of buying and selling requires improvement, mainly in its payment system.